Social Phobia in Nina LaCour's Novel Watch Over Me (2020) - Jafani, Raisa Hanifa; Anwar, Desvalini (Universitas Negeri Padang, 2024)
This research is an analysis of the novel Watch Over Me by Nina LaCour (2020). The analysis reveals the issue of social phobia which is one of the anxiety disorder types experienced by the main character in the novel. This research uses a descriptive qualitative method and the data is taken from quotations related to the topic. The theory used in this study is Psychoanalysis by Sigmund Freud, which examines how anxiety develops and is influenced by several factors in three parts of the human psyche: id, ego, and superego. The purposes of this research are to find out the symptoms of the main character’s social phobia, factors that influenced the causes of social phobia, and the role of peers in overcoming the social phobia suffered by the main character in the Watch Over Me novel. The result of this study is that the main character can overcome social phobia with the help of friends where she works.